2007
DOI: 10.3310/hta11480
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment to randomised trials: strategies for trial enrolment and participation study. The STEPS study

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
412
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(430 citation statements)
references
References 78 publications
11
412
1
6
Order By: Relevance
“…Reviews have reported that successful RCT recruitment is associated with a number of factors, including addressing clinically important questions at a timely point, employing dedicated research staff, ensuring that staff are trained about trial processes and interventions, and having straightforward data collection [9,10]. In addition, effective strategies to improve recruitment include telephone reminders, financial incentives, open-trial designs where participants know which treatment they are receiving in the trial, and use of opt-out rather than opt-in procedures [3].…”
Section: Introductionmentioning
confidence: 99%
“…Reviews have reported that successful RCT recruitment is associated with a number of factors, including addressing clinically important questions at a timely point, employing dedicated research staff, ensuring that staff are trained about trial processes and interventions, and having straightforward data collection [9,10]. In addition, effective strategies to improve recruitment include telephone reminders, financial incentives, open-trial designs where participants know which treatment they are receiving in the trial, and use of opt-out rather than opt-in procedures [3].…”
Section: Introductionmentioning
confidence: 99%
“…The STEPS study which investigated strategies for trial enrolment and participation, found only 31% of randomised controlled trials (RCTs) recruited to time and target. 2 A review by Treweek and colleagues recognised that achieving recruitment is an issue in medical research, and that knowledge on how to increase recruitment at sites participating in a trial is currently lacking. 3 This challenge was further reinforced by a recent survey of Clinical Trials Units Directors where "research into methods to boost recruitment in trials" was found to be their highest research priority.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulties of recruiting participants to clinical trials are well documented; [12][13][14][15][16][17][18][19] it is suggested that around 50% of clinical trials fail to reach their recruitment target, or require extension. 12 Patient-related factors have been identified to explain this, such as a lack of understanding about research or medical condition; concerns with the research process, especially randomisation; preference for particular treatments; and a perception that research is inappropriate for serious medical conditions.…”
Section: Introductionmentioning
confidence: 99%